Modelling mobility in emergency scenario for MANET applications - Srivastava A.; Kumar D.; Gupta S.C. (My University, 2025)
In a post disaster situation, movement of rescue teams should be modelled effectively to ensure proper communication and co-ordination amongst different teams. For this it is necessary that movement is modelled effectively. In this paper we propose an emergency scenario movement modelling by managing the co-ordination task by a four way directional movement. The communication between the stages is considered to be provided by a MANET based network setup, since they are easy to deploy and do not require elaborate infrastructure. Mobility of MANET nodes between the stages has been modeled with random waypoint mobility model (RWM). Performance of the scenario is analyzed for three routing protocols viz. LAR [1], DYMO [2] and AODV [3]. Packet delivery ratio, end to end delay, normalized routing load and data packets forwarded is estimated for these protocols. From the results it is observed that for such situations, performance of geographic routing protocols is better than other reactive protocols. © 2014 IEEE.